Kinerja Reproduksi Ternak Kuda Kerja di Kabupaten Bantul, Daerah Istimewa Yogyakarta (Reproductive Performances of Working Mare at Bantul Regency, Yogyakarta Special Province) - Arif Setyobudi; Kustono (Kustono); Diah Tri Widayati (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
The experiment was conducted to determine reproductive performances of working mare at Bantul Regency, Yogyakarta Special Province. One hundred and fourten mares were used in the experiment coming from 94 respondens.Samples were collected from district of Sewon, Banguntapan and Pleret. The parameters observed were first mating age, service per conception (S/C), postpartum mating (PPM), foaling interval (F/I), body weight, working hours, andfeed consumption. The collected data were analyzed descriptively. The average of first mating age, service per conception (S/C), postpartum mating (PPM), foaling interval (FI) were 31.42±4.62 months, 2.85±0,81; 94.69±32.42days; 493.65 ± 43.01 days (ranged in 1-5 S/C; 35-180 days; 395-594 days); body weight, working hours, and feed consumption were 273.65±43.64 kg, 8 hours 11 minutes/day, 16.02±2.17 kg respectively. The conclusion of theexperiment were that the reproductive performances of working horse at Bantul Regency in Daerah Istimewa Yogyakarta is generally less than the normal performances reproductive of horse.(Key words: Reproduction performance, Working horse, Bantul Regency)